Combined Two-Model CFD Simulation of Trickle Bed Reactors with Head-Sump Extension: Case Study on Hydrodynamics and Biological Methanation - Markthaler, Simon; Plankenbühler, Thomas; Miederer, Jonas; Kolb, Sebastian; Herkendell, Katharina; Karl, Jürgen (Industrial & Engineering Chemistry Research, 2022)
Trickle bed reactors are one of the world’s most employed technologies for multiphase processing, and they have been scrutinized for decades. However, accurate prediction and scale-up of trickle bed reactors are still challenging owing to complex interactions of multiphase flow, interfacial mass transfer, and reaction kinetics. The present computational model provides an insight into process phenomena on the basis of Eulerian–Eulerian methodology. It captures all parts of a trickle bed reactor─packing, head, and sump─which enables simulation of co- and countercurrent flow, gas or liquid recycle, and arbitrary retention time. Applying this model, hydrodynamic simulations reveal an improved prediction of liquid holdup, liquid dispersion, and pressure drop compared to CFD models of only the trickle bed. Furthermore, the interfacial surface area is analyzed and validated on account of a literature correlation. Exemplifying the entire approach with chemical absorption and reaction, the simulation of biological methanation presents methane concentration and productivity which are of the same order of magnitude as experimental data for an operating pressure of pop = 0.1–1 MPaabs.<br

Comparative analysis of biological methanation utilizing mixed and pure cultures in a lab-scale trickle-bed reactor - Schindhelm, Lucas; Weidlich, Tobias; Trabold, Thomas; Herkendell, Katharina; Karl, Jürgen (6th Doctoral Colloquium Bioenergy, 2023)

Domination of volumetric toughening by silver nanoparticles over interfacial strengthening of carbon nanotubes in bactericidal hydroxyapatite biocomposite - Herkendell, Katharina; Shukla, Vishnu Raj; Patel, Anup Kumar; Balani, Kantesh (Materials Science and Engineering C, 2014)
In order to address the problem of bacterial infections in bone-substitution surgery, it is essential that bone replacement biomaterials are equipped with bactericidal components. This research aims to optimize the content of silver (Ag), a well-known antibacterial metal, in a multiwalled carbon nanotube (CNT) reinforced hydroxyapatite (HA) composite, to yield a bioceramic which can be used as an antibacterial and tough surface of bone replacement prosthesis. The bactericidal properties evaluated using Escherichia coli and Staphylococcus epidermidis indicate that CNT reinforcement supports growth of Gram negative E. coli bacteria ( 8.5% more adhesion than pure HA); but showed a strong decrease of Gram positive S. epidermidis bacteria ( diminished to 66%) compared to that of pure HA. Small amounts of silver (2-5 wt.%) already show a severe bactericidal effect when compared to that of HA-CNT (by 30% and 60% respectively). MTT assay confirmed enhanced biocompatibility of L929 cells on HA-4 wt.% CNT ( 121%), HA-4 wt.% CNT-1 wt.% Ag ( 124%) sample and HA-4 wt.% CNT-2 wt.% Ag ( 100%) when compared to that of pure HA. The samples with higher silver content showed decreased biocompatibility (77% for HA-4 wt.% CNT-5 wt.% Ag sample and 73% for HA-4 wt.% CNT-10 wt.% Ag). Though reinforcement of 4 wt.% CNT has shown an increase of fracture toughness by 62%, silver reinforcement has shown enhancement of up to 244% (i.e. 3.43 times). Accordingly, isolation of toughening contribution indicates that volumetric toughening by silver dominates over interfacial strengthening contributed by CNTs towards enhanced fracture toughness of potential HA-Ag-CNT biocomposites. © 2013 Elsevier B.V.
CRIS-Team Scopus Importer:2021-03-08
Keywords: Antibacterial; Carbon nanotubes (CNTs); Cytocompatibility; Fracture toughness; Hydroxyapatite (HA); Silver (Ag)

Earth's most needed uncultivated aquatic prokaryotes - Simon, Sophie A.; Aschmann, Vera; Behrendt, Annika; Hügler, Michael; Engl, Lisa M.; Pohlner, Marion; Rolfes, Sönke; Brinkhoff, Thorsten; Engelen, Bert; Könneke, Martin; Rodriguez-R, Luis M.; Bornemann, Till L.V.; et al. (Water Research, 2025)
Aquatic ecosystems house a significant fraction of Earth's biosphere, yet most prokaryotes inhabiting these environments remain uncultivated. While recently developed genome-resolved metagenomics and single-cell genomics techniques have underscored the immense genetic breadth and metabolic potential residing in uncultivated Bacteria and Archaea, cultivation of these microorganisms is required to study their physiology via genetic systems, confirm predicted biochemical pathways, exploit biotechnological potential, and accurately appraise nutrient turnover. Over the past two decades, the limitations of culture-independent investigations highlighted the importance of cultivation in bridging this vast knowledge gap. Here, we collected more than 80 highly sought-after uncultivated lineages of aquatic Bacteria and Archaea with global ecological impact. In addition to fulfilling critical roles in global carbon, nitrogen, and sulfur cycling, many of these organisms are thought to partake in key symbiotic relationships. This review highlights the vital contributions of uncultured microbes in aquatic ecosystems, from lakes and groundwater to the surfaces and depths of the oceans and will guide current and future initiatives tasked with cultivating our planet's most elusive, yet highly consequential aquatic microflora.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Aquatic; Archaea; Bacteria; Cultivation; Uncultivated

Electrochemical evaluation of different polymer binders for the production of carbon-modified stainless-steel electrodes for sustainable power generation using a soil microbial fuel cell - Simeon, Imologie M.; Herkendell, Katharina; Pant, Deepak; Freitag, Ruth (Chemical Engineering Journal Advances, 2022)
In this study, four different polymeric binders - polytetrafluoroethylene (PTFE), two-component epoxy (epoxy), polyvinyl alcohol (PVA), and polyvinylidene fluoride (PVDF) - were used to fabricate a surface-modified stainless-steel electrode. The polymeric binders were used to bond highly conductive carbon-black to a stainless-steel support using a simple fabrication method. The performance of the electrodes in terms of sustainable power generation was tested in a soil microbial fuel cell (SMFC). PTFE showed the fastest and best initial response in no-load operation, reaching a voltage of 370 mV after 7 days, compared to epoxy, PVA, and PVDF, which had 163, 151.7, and -26.7 mV, respectively. Electrochemical measurements showed that epoxy and PVDF have similar redox potential when operated as anode and cathode in an SMFC. Electrochemical evaluation of the long-term performance of the binders showed that epoxy gave 2.2-, 3.4-, and 4.9-fold higher performance than PVDF, PTFE, and PVA, respectively, under intermittent polarization. Although PVDF did not perform well in open circuits, it produced the highest current density in continuous operation with external loads. The most sustained performance was obtained with epoxy. This study has shown that epoxy can be a suitable and eco-friendly substitute for other binders using a simple fabrication method to produce high-performance anodes and cathodes for sustainable bioelectricity generation with a SMFC.
CRIS-Team Scopus Importer:2022-03-18
Keywords: bioelectricity; Electrochemical; Electrode; Microbial fuel cell; Polymer binder; Soil; Sustainable performance

Electrochemical Impedance Spectroscopy as a Characterization Method for Enzymatic Fuel Cell Bioanodes - Torrigino, Federica; Nagel, Marcel; Hartmann, Martin; Herkendell, Katharina (ChemElectroChem, 2024)
Enzymatic fuel cells (EFCs) offer renewable energy conversion via highly selective electrode reactions using enzymes as natural catalysts even under mild conditions. Electrochemical impedance spectroscopy (EIS) is a valuable tool for evaluating EFC performance, providing insights into substrate mass transport, enzyme kinetics, and electrode stability. Despite its acknowledged importance, the use of EIS coupled with distribution of relaxation times (DRT) analysis in EFCs research is limited. Our study addresses this gap by employing EIS and DRT analysis to investigate enzyme-based anodic processes, focusing on the bioelectrocatalytic oxidation of glucose catalyzed by glucose oxidase (GOx). Through careful variation of multiple parameters, it was possible to identify three distinct regions in the DRT plot. Each region has been subsequently associated with a key anodic process. The first region (R1) is associated with high-frequency phenomena occurring at the electrodes, primarily due to ionic conduction in the electrolyte. Intermediate-frequency processes are associated to charge transfer kinetics in region 2 (R2). Region 3 (R3) is linked to diffusion processes occurring at low frequencies. This thorough examination offers an insight into the functioning of enzymatic bioelectrodes, which in turn drives improvements in the design and components of biofuel cells to increase their power output.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Distribution of relaxation times; Electrochemical impedance spectroscopy; Enzymes; Fuel cells; Glucose oxidase

Environmental assessment of anaerobic digestion and biological methanation in power-to-methane systems - Elhaus, Nora; Kolb, Sebastian; Müller, Jakob; Goldbrunner, Markus; Karl, Jürgen; Herkendell, Katharina (Journal of Cleaner Production, 2023)
Biomethane can play a crucial role in achieving European climate goals and replacing natural gas. One way to increase biomethane production is through biological methanation, converting the remaining CO2 from biogas with hydrogen into methane. The required hydrogen is produced via electrolysis, making this technology also a valuable storage and balance solution for the energy grid. This study determines the ecological development potentials of biological methanation. For this purpose, different feedstock for anaerobic digestion are investigated as carbon source, effects of technological advances in electrolysis and biological methanation are determined and optimal modes of operation are evaluated. Results indicate that the biological methanation with an anaerobic digestion using manure as feedstock has the lowest greenhouse gas emissions. However, the biological methanation achieves the greatest reduction in emissions compared to traditional biomethane production (biogas upgrading with high pressurized water scrubbing) when using energy crops and reducing emissions from feedstock production. In the base scenario which represents the current state of technology, biogas from maize without additional methanation step produces 151.8 kgCO2eq/MWhCH4. In combination with biological methanation, biomethane can be produced in the future with CO2eq emissions of 121.4 kgCO2eq/MWhCH4. Other factors such as agricultural land occupation or water consumption show even more significant improvements. The main drivers of emissions are the electricity demand for the electrolysis and fugitive methane emissions. The study shows that there is great ecological potential in biological methanation, especially in the future with prognosed technological advances in electrolysis and biological methanation.
CRIS-Team Scopus Importer:2023-11-10
Keywords: Anaerobic digestion; Biological methanation; Biomethane; Greenhouse gas emission; Life cycle assessment; Methanogenesis; Power-to-Gas; Power-to-Methane; Renewable gases

Enzyme-capped relay-functionalized mesoporous carbon nanoparticles: Effective bioelectrocatalytic matrices for sensing and biofuel cell applications - Trifonov, Alexander; Herkendell, Katharina; Tel-Vered, Ran; Yehezkeli, Omer; Woerner, Michael; Willner, Itamar (ACS nano, 2013)
The porous high surface area and conducting properties of mesoporous carbon nanoparticles, CNPs (<500 nm diameter of NPs, pore dimensions ∼6.3 nm), are implemented to design electrically contacted enzyme electrodes for biosensing and biofuel cell applications. The relay units ferrocene methanol, Fc-MeOH, methylene blue, MB+, and 2,2′-azinobis(3- ethylbenzothiazoline-6-sulfonic acid), ABTS2-, are loaded in the pores of the mesoporous CNPs, and the pores are capped with glucose oxidase, GOx, horseradish peroxidase, HRP, or bilirubin oxidase, BOD, respectively. The resulting relay/enzyme-functionalized CNPs are immobilized on glassy carbon electrodes, and the relays encapsulated in the pores are sufficiently free to electrically contact the different enzymes with the bulk electrode supports. The Fc-MeOH/GOx CNP-functionalized electrode is implemented for the bioelectrocatalyzed sensing of glucose, and the MB+/HRP-modified CNPs are applied for the electrochemical sensing of H2O2. The ABTS2-/BOD-modified CNPs provide an effective electrically contacted material for the bioelectrocatalyzed reduction of O2 (kcat = 94 electrons·s-1). Integration of the Fc-MeOH/GOx CNP electrode and of the electrically wired ABTS2-/BOD CNP electrode as anode and cathode, respectively, yields a biofuel cell revealing a power output of ∼95 μW·cm-2. © 2013 American Chemical Society.
Created from Fastlane, Scopus look-up
Keywords: bilirubin oxidase; electrical wiring; glucose; mesoporous carbon; oxygen reduction; sensor

Extending the operational lifetimes of all-direct electron transfer enzymatic biofuel cells by magnetically assembling and exchanging the active biocatalyst layers on stationary electrodes - Herkendell, Katharina; Stemmer, Andreas; Tel-Vered, Ran (Nano Research, 2019)
Enzymatic biofuel cells promise green power generation from a variety of natural resources, yet these systems all suffer from time-dependent degradation effects, in particular progressing inactivation of enzymes, which severely limit the operational lifetimes of such power sources. To extend operational lifetimes, we introduce a method to magnetically exchange exhausted enzymes for fresh ones. To this end, anodic and cathodic enzymes or enzyme cascades are immobilized on carbon coated magnetic nanoparticles. Under the action of suitable magnetic field gradients, these nanoparticles are assembled on the respective stationary electrodes, or released from the electrodes for collection and subsequent exchange. We demonstrate this method on a fructose/oxygen consuming biofuel cell employing fructose dehydrogenase and bilirubin oxidase as well as on anodic and cathodic cascades employing fructose dehydrogenase/invertase and bilirubin oxidase/catalase, respectively. The enzyme-modified nanoparticles support direct electron transfer bioelectrocatalytic currents by wiring the redox active cofactors to the carbonaceous coating and from there to the electrode surfaces. The facile injection, assembly, and removal of enzyme-modified magnetic nanoparticles along with fuel solution provides a promising approach to extend the operational lifetime of enzymatic biofuel cells without the need for exchanging entire systems including chambers and electrodes. [Figure not available: see fulltext.].
Created from Fastlane, Scopus look-up
Keywords: direct electron transfer; enzymatic biofuel cell; enzyme cascade; lifetime; magnetic nanoparticle; recharge

In-situ electrochemical impedance analysis of a commercial SOFC stack fueled by real wood gas - Torrigino, Federica; Grimm, Fabian; Karl, Jürgen; Herkendell, Katharina (Heliyon, 2024)
The combination of solid oxide fuel cells (SOFCs) and wood gasification has the potential to significantly increase renewable electricity production and decrease emissions. Depending on the quality of the wood gas, degradation processes have a significant impact on the reliability and lifetime of the SOFC. Using electrochemical impedance spectroscopy (EIS) and subsequent distribution of relaxation times (DRT) analysis, the impact on the degradation of coupling wood gasification with a commercial SOFC stack is determined in this study. The thermal behavior of the SOFC stack under various operating conditions, as well as various synthetic wood gas mixtures classified by their hydrogen-to-carbon (H/C) ratio, was assessed. The decrease in the H/C ratio from 8 to 1, observed during syngas and real wood gas operation, leads to a rightward shift in the Nyquist plots, suggesting an increase in the SOFC stack's impedance. Correlations between variations in the H/C ratio and their effects on anodic electrooxidation, ionic conduction, gas transport, and diffusion were identified using DRT analysis to interpret the EIS results. By incorporating an upstream desulfurization system and ensuring an H/C ratio greater than 2, the coupling of biomass gasification with the SOFC stack was stable to degradation issues.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Biomass; Distributed power generation; Distribution of relaxation times (DRT); Electrochemical impedance spectroscopy (EIS); Solid oxide fuel cell (SOFC); Wood gas

Magnetically induced enzymatic cascades-advancing towards multi-fuel direct/mediated bioelectrocatalysis - Herkendell, Katharina; Stemmer, Andreas; Tel-Vered, Ran (Nanoscale Advances, 2019)
A generic method to magnetically assemble enzymatic cascades on electrode surfaces is introduced. The versatile method enables the simultaneous activation of both direct and mediated electron transfer bioelectrocatalysis to harness different substrates, which can serve as multiple fuels and oxidizers in biofuel cells generating clean energy.
Created from Fastlane, Scopus look-up

Next-Generation Proton-Exchange Membranes in Microbial Fuel Cells: Overcoming Nafion's Limitations - Sharma, Akshat; Đelević, Lara; Herkendell, Katharina (Energy Technology, 2024)
The adoption of microbial fuel cell (MFC) technology hinges on the development of efficient proton-exchange membranes (PEMs), which significantly influences fuel cell performance and cost. PEMs have a critical role in preventing oxygen crossover, maintaining electrochemical neutrality, and supporting microorganisms within MFCs. Nafion, the current industry-standard PEM, grapples with environmental, cost, and performance issues. Although improvements to Nafion have been reported using additives, immersion in heteropolyacids, different pretreatment methods, and UV irradiation, many of the challenges still remain. Herein, the recent developments in the area of alternative PEMs are reviewed and analyzed. Among them, sulfonated aromatic hydrocarbons, particularly sulfonated polyether ether ketone, have emerged as top contenders in terms of scale up and commercial viability. At the same time, membranes based on polyvinyl alcohol, ionic liquids, and natural materials are also being actively researched for various MFC applications. Since most studies are short term and lab scale, there is a need evaluate long-term stability and economic cost of PEMs in terms of standardized parameters such as power-to-cost and normalized energy recovery. Additionally, for emerging low-energy-density MFC applications like biosensors and in vivo power sources, PEM properties and design need to be tailored carefully.
CRIS-Team Scopus Importer:2024-03-29
Keywords: biofuel cells; cost analyses; membrane biofouling; membrane commercialization; microbial fuel cells; Nafion; proton exchange membranes

Status update on bioelectrochemical systems: Prospects for carbon electrode design and scale-up - Herkendell, Katharina (Catalysts, 2021)
Bioelectrochemical systems (BES) employ enzymes, subcellular structures or whole electroactive microorganisms as biocatalysts for energy conversion purposes, such as the electrosynthe-sis of value-added chemicals and power generation in biofuel cells. From a bioelectrode engineering viewpoint, customizable nanostructured carbonaceous matrices have recently received considerable scientific attention as promising electrode supports due to their unique properties attractive to bioelectronics devices. This review demonstrates the latest advances in the application of nano- and micro-structured carbon electrode assemblies in BES. Specifically, in view of the gradual increase in the commercial applicability of these systems, we aim to address the stability and scalability of different BES designs and to highlight their potential roles in a circular bioeconomy.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Bioeconomy; Bioelectrocatalysis; Bioelectrode; Bioenergy; Biofuel cells; Electrosynthesis; Enzyme; Mesoporous carbon; Microorganisms; Nanostructures; Waste valorization

Sustainably Sourced Mesoporous Carbon Molecular Sieves as Immobilization Matrices for Enzymatic Biofuel Cell Applications - Torrigino, Federica; Nagel, Marcel; Peng, Zhujun; Hartmann, Martin; Herkendell, Katharina (Catalysts, 2023)
Ordered mesoporous carbon CMK-3 sieves with a hexagonal structure and uniform pore size have recently emerged as promising materials for applications as adsorbents and electrodes. In this study, using sucrose as the sustainable carbon source and SBA-15 as a template, CMK-3 sieves are synthesized to form bioelectrocatalytic immobilization matrices for enzymatic biofuel cell (EFC) electrodes. Their electrochemical performance, capacitive features, and the stability of enzyme immobilization are analyzed and compared to commercially available multi-walled carbon nanotubes (MWCNT) using cyclic voltammetry and electrochemical impedance spectroscopy (EIS). The anodic reaction in the presence of glucose oxidase (GOx) and ferrocene methanol (FcMeOH) on the sustainably sourced CMK-3-based electrodes produces bioelectrocatalytic current responses at 0.5 V vs. saturated calomel electrode (SCE) that are twice as high as on the MWCNT-based electrodes under saturated glucose conditions. For the cathodic reaction, the MWCNT-based cathode performs marginally better than the CMK-3-based electrodes in the presence of bilirubin oxidase (BOD) and 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS2−). The CMK-3-based EFCs assembled from the GOx anode and BOD cathode results in a power output of 93 μW cm−2. In contrast, the output power of MWCNT-based EFCs is approximately 53 μW cm−2. The efficiency of CMK-3 as a support material for biofuel cell applications is effectively demonstrated.
CRIS-Team Scopus Importer:2024-12-16
Keywords: bilirubin oxidase; CMK-3; cyclic voltammetry (CV); electrochemical impedance spectroscopy (EIS); enzymatic biofuel cells (EFCs); glucose oxidase; immobilization; mesoporous carbon; MWCNT; sustainable carbon

Switchable aerobic/anaerobic multi-substrate biofuel cell operating on anodic and cathodic enzymatic cascade assemblies - Herkendell, Katharina; Tel-Vered, Ran; Stemmer, Andreas (Nanoscale, 2017)
Enzymatic fuel cells may become more accessible for applications powering portable electronic devices by broadening the range of potentially usable fuels and oxidizers. In this work we demonstrate the operation of an integrated, yet versatile multi-substrate biofuel cell utilizing either glucose, fructose, sucrose or combinations of thereof as biofuels, and molecular oxygen originating from solution phase and/or an internal chemical source, as the oxidizer. In order to achieve this goal we designed an enzymatic cascade-functionalized anode consisting of invertase (INV), mutarotase (MUT), glucose oxidase (GOX), and fructose dehydrogenase (FDH), deposited on top of a mesoporous carbon nanoparticle matrix, in which electron relay molecules had been entrapped. The anode was then conjugated to a compatible enzymatic cathode that employs a cascade of catalase (CAT) and bilirubin oxidase (BOD), allowing the cell to operate in an aerobic environment and/or to utilize, under anaerobic conditions for instance, hydrogen peroxide as a source for the oxygen oxidizer. While operated in the presence of the sugar mixture and hydrogen peroxide, the power output of the dually cascaded biofuel cell reaches a peak power density of 0.25 mW cm-2 and demonstrates an open circuit potential of 0.65 V. To our knowledge this is the first reported biofuel cell that discharges with both anodic and cathodic enzymatic cascade architectures and the first biofuel cell that is repeatedly switched between aerobic and anaerobic conditions without any significant decrease in the discharge performance.
Created from Fastlane, Scopus look-up

Techno-economic evaluation of anaerobic digestion and biological methanation in Power-to-Methane-Systems - Elhaus, Nora; Volkmann, Maximilian; Kolb, Sebastian; Schindhelm, Lucas; Herkendell, Katharina; Karl, Jürgen (Energy Conversion and Management, 2024)
Keywords: Power-to-Methane; Renewable gases; Methanogenesis; Power-to-Gas; Techno-economic assessment; Biological Methanation